1985
DOI: 10.1161/01.str.16.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Limb shaking--a carotid TIA.

Abstract: SUMMARY Eight patients are described with an unusual form of carotid transient ischemic attack, limb shaking. The basic features included a brief, involuntary, coarse, irregular, wavering movement or tremble involving arm-hand alone, or arm-hand and leg together. In 2 patients limb shaking was the initial manifestation of carotid occlusive disease, and all but one patient had other typical carotid transient ischemic attacks.Major atheromatous carotid occlusive disease was present in all patients on the side op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
2
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 11 publications
3
96
2
3
Order By: Relevance
“…Attacks appear to cease following carotid endarterectomy. 5 Transient focal cerebral ischemia has been the presumed explanation for these attacks, although hemodynamic studies have not been previously reported to support the specific role of perfusion insufficiency in the border zone territory.…”
mentioning
confidence: 99%
“…Attacks appear to cease following carotid endarterectomy. 5 Transient focal cerebral ischemia has been the presumed explanation for these attacks, although hemodynamic studies have not been previously reported to support the specific role of perfusion insufficiency in the border zone territory.…”
mentioning
confidence: 99%
“…When there is ipsilateral ICA occlusion, collateral flow to the MCA can occur from the contralateral ICA via the anterior communicating artery, the vertebrobasilar circulation via posterior communicating artery, or leptomeningeal anastomosis (LMA) from the above mentioned areteries [1,3]. The ECA can also supply collaterals from its maxillary or facial branches via ophthalmic artery, from the pterygopalatine network formed by the distal maxillary branches or, the oropharyngeal network formed by the ascending pharyngeal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Limb shaking is a rare manifestation of a transient ischemic attack (TIA) [1]. The atypical presentation in a patient with carotid occlusive disease may be mistaken for focal epilepsy, resulting in confusion or delayed diagnosis [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,40 A more specific type of TIA that has been documented in a few case reports is "orthostatic limb shaking" 13 which occurs on standing or neck-bending in 1 or more extremities, and is without electroencephalography correlate. 5,48,49,51 In the 3 most notable studies, 5 patients with limb-shaking were also shown to have decreased reactivity after inhaling CO 2 , 48 and another patient's symptoms resolved after endarterectomy. 51 In a study in which patients with this presentation were followed up over 2 years, the authors found that there was a 5-to 6-fold increased risk of stroke in these patients over those with carotid stenosis only.…”
Section: Literature Reviewmentioning
confidence: 99%